2020
DOI: 10.1108/jhr-05-2019-0103
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of colorectal cancer patients in postoperative recovery: integrative review

Abstract: Purpose The purpose of this paper is to synthesize the experiences and needs of colorectal cancer patients during postoperative recovery. Design/methodology/approach This study is an integrative review, conducted by CINAHL, PubMed, ScienceDirect and ThaiJO from 2009 to 2019. Ten research articles published have been selected by PRISMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…To our knowledge, this is the first study to encapsulate insights from both CRC patients and family caregivers to solicit a comprehensive understanding of their experiences and needs throughout the entire perioperative continuum. Like other cancers, the CRC diagnosis aroused a spectrum of unpleasant responses which were similar to those previously identified [ 5 , 9 , 16 , 17 , 23 ]. However, our study was unique in elucidating the deep-seated misconceptions and wrongful assumptions behind these negative emotions, which were more evident among the less-educated respondents.…”
Section: Discussionsupporting
confidence: 68%
“…To our knowledge, this is the first study to encapsulate insights from both CRC patients and family caregivers to solicit a comprehensive understanding of their experiences and needs throughout the entire perioperative continuum. Like other cancers, the CRC diagnosis aroused a spectrum of unpleasant responses which were similar to those previously identified [ 5 , 9 , 16 , 17 , 23 ]. However, our study was unique in elucidating the deep-seated misconceptions and wrongful assumptions behind these negative emotions, which were more evident among the less-educated respondents.…”
Section: Discussionsupporting
confidence: 68%
“…9,11,13 Knowledge about the patient's preoperative experience, perspectives and needs is of great value for professionals initializing CRC care pathways, as well as for professionals who seek to further optimize their CRC care pathways by offering holistic and patientcentred care which might prevent patient distress and help to cope with the cancer diagnosis and following treatment. 11,14 Therefore, the aim of this study was to explore the patient's experiences and perspectives on the preoperative surgical care pathway and the preoperative preparation for surgery and postoperative recovery, to truly tailor future CRC care to the patient's perioperative needs.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, little attention has been paid to the perspective of CRC patients on the current preoperative cancer care counselling, and how patients experience the period from diagnosis to surgery and recovery, both in clinical practice and in literature 9,11,13 . Knowledge about the patient's preoperative experience, perspectives and needs is of great value for professionals initializing CRC care pathways, as well as for professionals who seek to further optimize their CRC care pathways by offering holistic and patient‐centred care which might prevent patient distress and help to cope with the cancer diagnosis and following treatment 11,14 …”
Section: Introductionmentioning
confidence: 99%
“…Participants in this study also reported that they experienced a decrease in appetite at the beginning of the ostomy. bowel surgery contributes to the release of hormones that result in decreased appetite and resulting in weight loss (Changyai, Kongvattananon, & Somprasert, 2020).…”
Section: Discussionmentioning
confidence: 99%